The effect of ω-fatty acids on mrna expression level of PPARγ in patients with gastric adenocarcinoma - Hosseinzadeh, A.; Somi, M.-H.; Dolatkhah, H.; Esfahani, A.; Kafil, H.S.; Ardebili, S.M.M. (Experimental Oncology, 2016)
Background: The antineoplastic role of peroxisome proliferator-activated receptor gamma (PPARγ) ligandshas previously been demonstrated in several gastric cancer cell lines. Activation of PPARγ by polyunsaturated fatty acids (PUFAs) inhibits growth and proliferationof tumor cells. In this double-blind clinical study, we evaluate the effect of PUFAs on PPARγ mRNA expression in patients with gastric adenocarcinoma. Materials and Methods: A total of 34 chemotherapy-naive patients diagnosed with gastric adenocarcinoma were enrolled in the present study. According to treatment strategies, all subjects were divided into two groups, the first group (17 individuals) received cisplatin without supplements and the second group (17 individuals) received cisplatin plus orally administered PUFAs supplements for 3 weeks. The gastric biopsy samples were obtained from all participants before and after treatment, and PPARγ mRNA expression levels were evaluated by quantitative real-time polymerase chain reaction using validated reference genes. Results: Our findings revealed that PPARγ mRNA expression is significantly upregulated in group II afterreceiving cisplatin plus orally administered PUFAs supplements for three weeks (p < 0.0001), whereas PPARγ mRNA expression did not show significant alteration in group I after receiving cisplatin alone. Conclusion: The results of the study evidence that PPARγ may act as a potential target for the therapy of human gastric adenocarcinoma.